Current Immune-Related Molecular Approach in Combating Nasopharyngeal Cancer - Gondhowiardjo, Soehartati A. (World J Oncol, 2019)
Nasopharyngeal cancer is a cancer closely related to Epstein-Barr virus (EBV) infection. EBV protein has been shown to be related to various oncogenic development. Suppression of tumor suppressor genes, upregulating molecules to prevent immune attack, downregulating pro-apoptotic proteins, and stimulating local immune suppressive environment are among some roles that EBV proteins can exert on host cells. All those factors combined together with underlying genetic susceptibility of host cells further increase the chance of nasopharyngeal cancer development. Approach targeting those carcinogenesis pathways has been tested with marginal benefit. A newer approach boosting immune cells to increase recognition of tumor antigen and promoting cytotoxic T cell attack has shown promising clinical benefit. Further combination of those immunotherapies with other modality, in particular radiotherapy, has resulted in amplification of cancer killing.